A model for the management risks related to the implementation of insurance policies - Samira Ghazavi Dozein; Sanjar Salajegheh (Shahid Beheshti University of Medical Sciences, 2021)
Introduction: The aim of present study was to provide a model for evaluating the insurance policies of the Social Security Organization with a network governance approach. Methods: Through a mixed method study in Tehran and Golestan provinces, in first stage 35 people were selected among the experts and university professors and in second stage, 217 managers of insurance and health were included in the study. To achieve the optimal model four factors of network design, network formation, network health management and health network participation were identified and based on administrative, judicial and political evaluation, 18 questions were considered for each indicator. The data were analyzed through SPSS and LISREL software by exploratory factor analysis and path analysis. Results: Factor analysis showed the relationship between management risk indicators and dimensions of insurance risk, liquidity, credit, market, operational, national, reputation, legal, management, insurance and health and human resource factors. There was relationship between the indicators of level of implementation of policies and dimensions of human resources, investment, technology, market and information and communication technology. Among the sub-criteria of policy implementation, areas of investment, market, technical and human resources were ranked first to forth, and the information and communication technology area was ranked last. Conclusion: The results revealed that policy evaluation indicators, except for the judicial approach in the indicator of health network formation in network governance, are approved and could be introduced appropriate criterion for assessing network governance indicators defined to evaluate the insurance policies of the Social Security Organization.